2016
DOI: 10.21547/jss.265494
|View full text |Cite
|
Sign up to set email alerts
|

Examining EFL Teacher Candidates’ Conceptions of English Language Teachers through Metaphors

Abstract: This study aims to investigate EFL teacher candidates' metaphors regarding English language teachers. The data was collected through 102 teacher candidates' essays written on their views of being an EFL teachers and teaching. The metaphors were qualitatively and quantitatively analyzed. Content analysis of the essays revealed a total of 134 metaphors categorized in four groups: people, objects, actions and animals. The verbs, adjectives and adverbs in the host statements of metaphors were also investigated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…When we look at the findings related to teacher, student, parent, school, school principal, curriculum and teaching materials concepts as the inputs of the education system, it was observed that PFCP and education faculty students provided very similar responses to each other except the curriculum concept, and these responses were found to be positive except parent and school concepts. The findings related to the concept of teacher are similar to those reported in many other studies (Çocuk, Yokuş & Tanrıseven, 2015;Ekiz & Koçyiğit, 2013;Ma & Gao,2017;Pektaş & Kıldan, 2009;Polat, 2013;Saban, 2004;Saban, Koçbeker & Saban, 2006;Yalçın Arslan & Cinkara, 2016). Especially in the study carried out by Saban, Koçbeker & Saban (2006), the prospective teachers of English described "guide and advisor" roles of teachers through counsellor, light, chief conductor, mother, compass and leader metaphors.…”
Section: Discussion Conclusion and Implementationsupporting
confidence: 89%
See 2 more Smart Citations
“…When we look at the findings related to teacher, student, parent, school, school principal, curriculum and teaching materials concepts as the inputs of the education system, it was observed that PFCP and education faculty students provided very similar responses to each other except the curriculum concept, and these responses were found to be positive except parent and school concepts. The findings related to the concept of teacher are similar to those reported in many other studies (Çocuk, Yokuş & Tanrıseven, 2015;Ekiz & Koçyiğit, 2013;Ma & Gao,2017;Pektaş & Kıldan, 2009;Polat, 2013;Saban, 2004;Saban, Koçbeker & Saban, 2006;Yalçın Arslan & Cinkara, 2016). Especially in the study carried out by Saban, Koçbeker & Saban (2006), the prospective teachers of English described "guide and advisor" roles of teachers through counsellor, light, chief conductor, mother, compass and leader metaphors.…”
Section: Discussion Conclusion and Implementationsupporting
confidence: 89%
“…In the studies that investigated perceptions of prospective teachers on Turkish education system, the system has been dealt with either as a whole (Kasapoğlu, 2016;Örücü, 2014) or based on the constituents of the system including the concepts of teacher (Çocuk, Yokuş & Tanrıseven, 2015;Ekiz & Koçyiğit, 2013;Ma & Gao,2017;Pektaş & Kıldan, 2009;Polat, 2013;Saban, 2004;Saban, Koçbeker & Saban, 2006;Yalçın Arslan & Cinkara, 2016), student (Bozkl,2002;Saban, 2009;Sezgin, et al 2014;Hoffman & Kretovics,2004), school (Aydoğdu, 2008;Cerit, 2006;Inbar, 1996;Mahlios & Maxon, 1998;Saban, 2008;Örücü, 2014;Özdemir, 2012), school principal (Günbayı, 2011;Konan & Yılmaz, 2016;Yalçın, 2011), curriculum (Gültekin, 2013;Örten & Erginer, 2016;Özdemir, 2012), materials (Eren & Tekinaslan,2013), classroom management (Akar & Yıldırım, 2009), assessment and evaluation (Acar Güvendir & Özer Özkan, 2016;Harris, Harnett & Brown,2009;Karaşahinoğlu, 2015;Tatar & Murat,2011;Tekinarslan, 2013;Taşdemir & Taşdemir,2016), ethics (Altınkurt & Yılmaz, 2011;Dinç, 2016;Gençoğlu, 2015;Mısırlı, 2016) were handled one by one. However, another important point of this study is to discuss all the concepts of t...…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies on how the concept of "teacher" is perceived by the students, pre-service teachers, administrators and the shareholders in the literature (Cerit, 2008;Çakmak, 2021;Çelikten, 2006;Oğuz, 2009;Peretz, Mendelson and Kron, 2003;Sökmen, Kılıç and Yıldırım, 2020;Yalçın-Arslan and Cinkara, 2016). Most of these studies, which adopted a qualitative research method, were conducted without reaching a large number of people.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while in some studies EFL teachers' knowledge provider roles were featured (Kavanoz, 2016;Yalçın-Arslan & Cinkara, 2016), in some others, they were mainly identified through their roles as a guide (Yeşilbursa, 2012;Sayar, 2014). Each metaphor, and by extension, each study of metaphor can communicate only a part of the complexity of the phenomenon and classroom realities (Marshall, 1990).…”
Section: Introductionmentioning
confidence: 99%